FAMILIES OF BEE IN THE CLIMATE CONDITIONS OF UZBEKISTAN FEEDING AND BREEDING TECHNOLOGY - R. K. Jamolov; R. O. Azizov; I. R. Mamanabiev (Journals Park Publishing, 2024)
In the article, when working with a bee family, first of all, it is necessary to follow all the rules, not to disturb the peace of the bee family, (when the air temperature is low, when there is no nectar in nature), it is necessary not to over-excite them, otherwise, the bees will be disturbed and sting more. information about the possibility of obtaining bee families and the use of technological methods of breeding bee families during the time when the juice comes from nature.
Keywords: pollen, wax, care, peace, disturbance, wind, oxygen, humidity, air temperature, working box, beekeeper's sting, catching tool, rotten bark, paper, match, carbon dioxide, sugar food , numbering, beekeeping journal.